The application of contract law principles in domestic contracts - Ibrahim, Norliah; Abd Ghadas, Zuhairah Ariff; Zakariah, Asri Amirul; Abdullah Asuhaimi, Farhanin (UPM Press, 2015)
A domestic contract refers to agreement between persons having family relationship and despite the general rule of contract, that parties in social, domestic and family agreements do not have intention to create legal relations, domestic contracts are legally binding. In the context of family law, domestic contracts normally involves marriage contracts and separation agreements which includes among others; pre-nuptial agreement, settlement agreement, division of matrimonial property agreement and custody of children agreement. Despite the common nature and structure of domestic contract as a typical agreement, there are concerns by the family law practitioners that domestic contracts should be interpreted differently from the commercial or other types of contract and judges should have special or additional factors of consideration in giving effect to the contracts.